Pathogenic Analysis of the Bronchoalveolar Lavage Fluid Samples With Pediatric Refractory Mycoplasma pneumoniae Pneumonia - Zhao, Fei (Front Cell Infect Microbiol, 2020)
Background: We conducted a pathogenic analysis in the bronchoalveolar lavage fluid (BALF) samples from refractory Mycoplasma pneumoniae pneumonia (RMPP) children. Methods: A total of 150 BALF samples from 60 RMPP patients were analyzed to investigate pathogenic changes. The characteristics of M. pneumoniae were analyzed through culture, real-time PCR, genotyping, antimicrobial susceptibility testing and proteomics. The other pathogens were determined using culture, sequencing and nucleic acid detection. Results: In 60 RMPP cases, the bacterial co-infection rate was 5%, while that of virus was 33.3%. The poor prognosis rate was 61.7%. The DNA positive rate among the 150 samples was 98.7%, while the culture positive rate was 56.7% for M. pneumoniae. Significant differences were noticed in the positivity of M. pneumoniae culture obtained from samples with a disease course of at least 3 weeks compared with those within 3 weeks. The genotype 1 M. pneumoniae strains showed a macrolide resistant (MLr) rate of 100%, and that for genotype 2 was 90.1%. Proteomics showed that there were 57 proteins up-regulated in the MLs M. pneumoniae, half of which were membrane-associated protein with adhesion or toxicity. Conclusions: Pediatric RMPP usually presented with viral co-infection, but it caused limited effects on the progression and prognosis of RMPP. Persistent presence of viable M. pneumoniae is not necessary in the later stage of RMPP. The expression of virulence factor in the MLr M. pneumoniae was higher than that of the MLs M. pneumoniae, which was more common in the RMPP children.